Impacto em custo-benefício do fornecimento gratuito de medicações para asma na população pediátrica - Koltermann, Vanessa (2020)
Introduction: Asthma is one of the most common chronic diseases in childhood, generating high costs for the health system and for society in general. Since June 2011, the Unified Health System (SUS) has started to provid asthma medicines. This study evaluates the impact on the reduction of hospitalizations from the availability of government subsidized asthma medications in the pediatric population from 1 to 19 years old, stratifying by age and region of the country. In addition, the cost-benefit of the after institution of the program of distribution of asthma medicines is analyzed. Methods: This is a descriptive study, based on information from the Department of Informatics of the Unified Health System (DATASUS). Incidence of hospitalizations and cost of patients aged 1-19 years with asthma diagnosis were compared pre (2008-2010) and post (2012-2017) supply of government subsidized inhaled medications (beclomethasone). Results: The asthma admission rate reduced by 28.4% when comparing the two periods (OR 0.71; 95% CI 0.64-0.79). Children aged 1 to 4 years had a 27.3% reduction in asthma admissions (OR 0.72; 95% CI 0.63-0.82), while those aged 15 to 19 years had a 39.65% decrease (OR 0.59; 95% CI 0.37-0.95). Asthma admission costs decreased when comparing the two periods (OR 0.68; 95% CI 0.62-0.74). After the introduction of the program, mean cost savings reached US $27,865,905.08 in children aged 1 to 4 years and US $21,350,660.63 in those aged 5 to 19 years. Conclusions: Pediatric asthma imposes a significant economic burden on the Brazilian public health system. From 2012 to 2015, the government distribution of inhaled corticosteroids was cost-effective in all ages analyzed. In 2017, it was not cost-effective in this population, only effective in reducing hospitalizations due to asthma.